PENGARUH KEJELASAN SASARAN ANGGARAN, PARTISIPASI PENYUSUNAN ANGGARAN, AKUNTABILITAS TERHADAP KINERJA MANAJERIAL DAN KINERJA ANGGARAN PADA DINAS PEKERJAAN UMUM PENATAAN RUANG, PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN BARITO TIMUR - MALASARI, KELI MALASARI (JURNAL KINDAI, 2023)
Abstract: Keli Malasari, The Effect of Clarity on Budgetary Targets, Participation in Budgeting, Accountability for Managerial Performance and Budget Performance at the Office of Public Works Spatial Planning, Housing and Residential Areas of East Barito Regency, Main Advisor: Ujianto, Assistant Advisor: Dahliana Iskandar This study aims to examine the effect of Clarity on Budgetary Targets, Participation in Budgeting, Accountability on Managerial Performance and Budget Performance as intervening variables on employees of the Office of Public Works Spatial Planning, Housing and Residential Areas of East Barito Regency The population in this study were 53 civil servants, the data were taken from questionnaires distributed to respondents. Data were analyzed using SmartPLS Version 3. The results of this study are clarity of budgetary goals affects managerial performance, budgeting participation affects managerial performance, accountability affects managerial performance, clarity of budgetary goals affects budgetary performance, budgeting participation affects budgetary performance, accountability affects budgetary performance, managerial performance influence on budget performance, Managerial Performance mediates the influence of clarity of budget targets on budget performance, Managerial Performance mediates the influence of budgetary participation on budget performance, Managerial Performance mediates the effect of accountability on budget performance at the Office of Public Works, Spatial Planning, Housing and Residential Areas of East Barito Regency Keywords: Budget Targets, Participation, Budgeting, Accountability, Managerial Performance, Budget Performance